2020
DOI: 10.1186/s13002-020-00406-z
|View full text |Cite
|
Sign up to set email alerts
|

The uses of fig (Ficus) by five ethnic minority communities in Southern Shan State, Myanmar

Abstract: Background Most regions of Myanmar fall within the Indo-Burma Biodiversity Hotspot and are threatened with biodiversity loss. Development of a comprehensive framework for sustainable development is crucial. Figs are ecological keystone species within these regions and are also important for traditional spiritual food and health uses, which often have accompanying conservation practices. The traditional use and management of figs may offer clues to help guide the development of national policies for sustainable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Local livelihoods are based on paddy cultivation in small lowland basins and shifting cultivation of vegetables on the surrounding hillsides. These shifting cultivation practices are now giving way to the permanent cultivation of cash crops such as tea, oranges, and pears (Mon et al 2020). Despite these changing practices, the harvesting of wild subsistence resources from forests is still common and plays an important role in the daily lives of local people.…”
Section: Field Sites and Methodologymentioning
confidence: 99%
“…Local livelihoods are based on paddy cultivation in small lowland basins and shifting cultivation of vegetables on the surrounding hillsides. These shifting cultivation practices are now giving way to the permanent cultivation of cash crops such as tea, oranges, and pears (Mon et al 2020). Despite these changing practices, the harvesting of wild subsistence resources from forests is still common and plays an important role in the daily lives of local people.…”
Section: Field Sites and Methodologymentioning
confidence: 99%
“…According to the data recorded, many traders 94.4% (n = 68) reported that they do not experience any challenges when trading with prickly pears, while the remaining 5.5% (n = 4) reported that they sometimes encounter challenges, such as customers wanting to bargain over the price, disputes over the use of the trading space with Nefzaoui & Ben Salem, 2002;Saenz, 2000;Sáenz, 2002;Yahia & Sáenz, 2011). The use of wild fruits is a common phenomenon around the world, as observed by Mon et al (2020). The lack of knowledge about the status of O. ficus-indica as an alien plant is recognized in the literature .…”
Section: Does the Experience And Distance Involved In Collecting O Fi...mentioning
confidence: 99%
“…as a single species (Zhang, 2018). It uses for food and has socioeconomic importance, the near-ripe peeled or unpeeled fruits and young leaves of F. auriculata were sold such as in the north and central Vietnam (Mon, 2020).…”
Section: Article Historymentioning
confidence: 99%